A CONCEPTUAL FRAMEWORK FORTHE ALIGNMENT OF INNOVATION AND TECHNOLOGY - Pellissier,R (Universidad Alberto Hurtado. Facultad de Economía y Negocios, 2008)
Historically, business institutions base their growth strategies on their research and development (R&D) function.This function is fairly established and sets out to acquire new knowledge in a systematic process of research in order to produce or improve products,services or processes. In fact, innovation and research are two of the main thrusts for economic growth.The paper explores the convergence of innovation and research from a previous paper, focusing on the development of a conceptual model in terms of the technology (or knowledge) system required for the accomplishment of this convergence. In this sense, technology is defined as knowledge,tacit or explicit, in human, document or electronic format. The proposed convergence requires the use of knowledge systems to drive the innovation and research.The contribution of the paper lies in the knowledge developmental aspects of research and innovation convergence. An existing model to achieve for knowledge systems development will be reviewed and a modified versión presented after careful consideration of the body literature on knowledge and innovation systems.This model incorporates aspects of knowledge management as well as innovation and research management.